Ileo-ileal knotting masquerading as internal hernia: a rare cause of acute intestinal obstruction - Kumar, Manish; Khanna, Rahul; Meena, Ram N.; Mishra, Shashi P.; Panigrahy, Panchanana; Anand, Akshay; Kumar, Binod (International Surgery Journal, 2023)
Intestinal knotting is a rare cause of acute intestinal obstruction and in most cases is diagnosed intraoperatively due to its rarity and uncommon presentation. Out of different types of intestinal knots, ileo-ileal knotting is rarest and very few such cases have been reported in the literature. Due to very high mortality, early diagnosis and immediate surgical intervention are needed. Here we present a case of a 52-year-old male patient who presented with a history of non-passage of stool and flatus, after resuscitation patient was planned for exploratory laparotomy. Findings revealed gangrenous ileal loops and an ileo-ileal knot masquerading as an internal hernia. End-to-end anastomosis of the gangrenous ileum was done along with a decompressive proximal loop ileostomy. The patient was transferred to the intensive care unit after surgery. He died on postoperative day 1 due to metabolic acidosis with endotoxic shock. By reporting this case we want to emphasize on the need of keeping intestinal knots as a differential diagnosis while operating a case of acute intestinal obstruction.